Micropulse laser trabeculoplasty on Chinese patients with glaucoma or ocular hypertension: average 35 months follow-up results - Yuting Yang; Xinting Huang; Sheng Liao; Feng Zhang; Jingming Shi; Xuanchu Duan; Ke Liu (BMC Ophthalmology, 2022)
Abstract Background Glaucoma is a group of eye diseases that can damage the optic nerve and cause vision loss. A novel technology micropulse laser trabeculoplasty (MLT) can use duty-circle subvisible laser pulses to treat glaucoma. The aim of this study is to evaluate the efficacy of 360° MLT to alleviate intraocular pressure (IOP) in patients with glaucoma. Methods This was a single-center prospective study on patients treated with 360° MLT using a Diode True-Yellow 577-nm Laser with MicroPulse technology. All the patients were recruited from the Department of Ophthalmology. Follow-up visits were carried out at 1 day, 1 week, 1 month, 3 months, 6 months, 18 months, and 36 months after the procedure. Best-corrected visual acuity (BCVA), Intraocular pressure (IOP), and vertical cup-to-disc ratio (C/D ratio) were measured during the follow-up. Repeated-measures analysis of variance (ANOVA) and Kaplan–Meier analysis were performed to evaluate the outcomes. Results A total of 39 eyes from 25 patients were included in this study (10 men/15 women). The average age of patients was 41.47 ± 14.39 years old, and the baseline IOP was 21.13 ± 7.75 mmHg. MLT significantly reduced the IOP at 1 day (range 15.61–19.01, P = 0.0218), 3 months (range 16.47–19.22, P = 0.0390), and 6 months (range 15.38–18.56, P = 0.0332) compared with the baseline. However, by the end of the study, only 21.88% of patients demonstrated a ≥ 20% IOP reduction, while seven eyes needed further laser or surgical treatment. The IOP of glaucoma patients was significantly lower than the ocular hypertension patients at 1 month (P = 0.0124), 3 months (P = 0.0004), 18 months (P = 0.0061) and 36 months (P = 0.0119). Conclusions Micropulse laser trabeculoplasty reduce IOP in patients with glaucoma or ocular hypertension for a short period, but its lowering efficiency is limited up to 6 months of the follow-up period.